(untitled) (African Journal of Science, Technology and Social Sciences, 2024)
The Forest Sector is Key to Kenya’s social and economic well-being since most of the financial activities rely on environmental-based resources for their sustenance. The Forest Conservation and Management Act, of 2016, provides for the conservation and management of public, community, and private forests. This has brought a paradigm shift in forest management from central command to involving various stakeholders. Adequate stakeholders’ engagement in the direction of forest resources, results in minimal conflicts. Local involvement promotes a sense of ownership to the Forest Adjacent Communities Consequently, reducing conflicts in the management of the forest resources. This dissertation focuses on the impacts of logging moratorium on Community Forest Associations in our state forests, with a focus of two CFAs in Meru County. It uses both quantitative and qualitative research design. An in-depth literature review was, used to enrich the research findings. Data was collected from 289 Mucheene and Ruthumbi CFA residents. Their views on the impacts of logging moratorium to the CFA were also documented. The study found out that forest conservation cannot be delinked from livelihood improvement by the Forest Adjacent Communities. There lie difficulties for the area population of the study area to support their life demands with the moratorium in place owing to the fact that they highly depended on the forest to support their livelihoods pre-moratorium. The study found that 93.4 % of the respondents believe that legal logging promotes job creation in the sawmill value chain circular economy. Findings are expected, to inform policy on forest conservation in collaboration with the FAC. The study recommends that the Government should adopt a regulation mechanism that safeguards logging in the extension forest of the community whenever there is an ongoing logging moratorium in the public forest. Communities, Forests, Logging, Moratorium, Livelihoods, Stakeholders engagement.